Effect of maternal dyslipidaemia on the cardiorespiratory physiology and biochemical parameters in male rat offspring. Issue 11 (27th November 2017) - Guimarães, Keyth Sulamitta L.; de Araújo, Emmanuel Veríssimo; Aquino, Jailane Souza; Gadelha, Danilo Assis; Balarini, Camille Moura; Costa-Silva, João Henrique; Magnani, Marciane; Vidal, Hubert; Braga, Valdir Andrade; de Brito Alves, José Luiz
Abstract: The present study evaluated the effects of maternal dyslipidaemia on blood pressure (BP), cardiorespiratory physiology and biochemical parameters in male offspring. Wistar rat dams were fed either a control (CTL) or a dyslipidaemic (DLP) diet during pregnancy and lactation. After weaning, both CTL and DLP offspring received standard diet. On the 30th and 90th day of life, blood samples were collected for metabolic analyses. Direct measurements of BP, respiratory frequency (RF ), tidal volume (VT ) and ventilation (VE ) under baseline condition, as well as during hypercapnia (7 % CO2 ) and hypoxia (KCN, 0·04 %), were recorded from awake 90-d-old male offspring. DLP dams exhibited raised serum levels of total cholesterol (TC) (4·0-fold), TAG (2·0-fold), VLDL+LDL (7·7-fold) and reduced HDL-cholesterol (2·4-fold), insulin resistance and hepatic steatosis at the end of lactation. At 30 d of age, the DLP offspring showed an increase in the serum levels of TC ( P <0·05) and VLDL+LDL ( P <0·05) in comparison with CTL offspring. At 90 d of age, DLP offspring exhibited higher mean arterial pressure (MAP, approximately 34 %). In the spectral analysis, the DLP group showed augmented low-frequency (LF) power and LF:high-frequency (HF) ratio when compared with CTL offspring. In addition, the DLP animals showed a larger delta variation in arterial pressure after administration of the ganglionic blocker ( P =0·0003). We also found that cardiorespiratory response to hypercapnia and hypoxia was augmented in DLP offspring. In conclusion, the present data show that maternal dyslipidaemia alters cardiorespiratory physiology and may be a predisposing factor for hypertension at adulthood.